Air pollution with PM10 particles in Maribor, Ljubljana and Koper in the period 2005–2014 - Rebernak , Uroš (Journal for Geography, 2017)
Air pollution has a large impact on health and well-being of people, and it affects other living organisms, as we cannot avoid the air that we breathe. Sulphur dioxide was considered the most problematic pollutant in the past. After introduction of fuels with low sulphur content and implemented measures in thermal power plants and in industry, we no longer have problems with sulphur in Slovenia. Ozone pollution and PM10 particles pollutions are currently the most serious ones in Slovenia. The article analyses annual and daily regimes of PM10 particles in Maribor, Ljubljana, and Koper in the period 2005-2014. It interprets the linear trend of PM10 particles trend, compares average values of PM10 particles in all three measuring locations, and analyses the examples of daily regimes of extremely high PM10 particles concentration caused by the fireworks and use of private pyrotechnics.